Surgical treatment of GERD. Comperative study of WTP vs. Toupet fundoplication – results of 151 consecutive cases - Tadeusz Wróblewski; Konrad Kobryn; Małgorzata Nowosad; Marek Krawczyk (Videosurgery and Other Miniinvasive Techniques)
Introduction: Gastroesophageal reflux disease (GERD) is recognized as one of the most common disorders of the upper gastrointestinal tract (GIT). The best choice of management for advanced GERD is laparoscopic surgery. Aim : To compare and evaluate the results of surgical treatment of GERD patients operated on using two different techniques. Material and methods : Between 2001 and 2012, 353 patients (211 female and 142 male), aged 17–76 years (mean 44), underwent laparoscopic antireflux surgery. The study included patients who underwent a Toupet fundoplication or Wroblewski Tadeusz Procedure (WTP). Results: The mean age of the group was 47.77 years (17–80 years). Forty-nine (32.45%) patients had severe symptoms, 93 (61.58%) had mild symptoms and 9 (5.96%) had a single mild but intolerable sign of GERD. Eighty-six (56.95%) patients had a Toupet fundoplication and 65 (43.04%) had a WTP. The follow-up period was 18–144 months. The average operating time for Toupet fundoplication and the WTP procedure was 164 min (90–300 min) and 147 min (90–210 min), respectively. The perioperative mortality rate was 0.66%. The average post-operative hospitalization period was 5.4 days (2–16 post-operative days (POD) = Toupet) vs. 4.7 days (2–9 POD = WTP). No reoperations were performed. No major surgical complications were identified. Conclusions : Wroblewski Tadeusz Procedure due to a low percentage of post-operative complications, good quality of life of patients and a zero recurrence rate of hiatal hernia should be a method of choice.